Cost analysis of a simulation-based training for health workforce in India - Gursimer Jeet; Shankar Prinja; Arun Kumar Aggarwal (Wolters Kluwer Medknow Publications, 2017)
Background: Training of health-care workforce including doctors, staff nurses, and Auxiliary Nurse Midwives using simulation techniques for skill enhancement have been used in a variety of clinical settings to improve the quality of training. India adopted the skills laboratories model for capacity building of health workers in maternal and child health in Bihar state. Objective: Current economic evaluation was performed with the objective of assessing the financial and economic cost of implementing skills laboratories. Methods: Data on all resources spent for the development of skill laboratory and implementing training during financial year 2011 were collected from Patna district in Bihar state. We used standard methods to estimate the full financial and economic costs of implementing the skills laboratories from a health system perspective. Results: Overall cost of implementing 20 permanent and 10 mobile skills laboratory training in Bihar was Indian Rupee (INR) 8849895 from a financial perspective. The cost was nearly two times higher when using an economic perspective to account for opportunity cost of all resources used. The unit cost of training a participant using permanent and mobile laboratory was INR 6856 and INR 7474, respectively assuming an annual volume of 90 training. The optimum number of training which should be operated annually in a skills laboratory to make it most efficient is about 70-80 training per annum. Conclusions: Economic implications of skills laboratory organization should be borne while planning scale up in Bihar and other states. Further research on the effectiveness of two models of skill laboratory, that is, permanent and mobile and their cost is recommended.